Prevalence and correlates of HIV testing among adolescents 10–19 years in a post-conflict pastoralist community of Karamoja region, Uganda - Ssebunya, Rogers N.; Wanyenze, Rhoda K.; Namale, Leticia; Lukolyo, Heather; Kisitu, Grace P.; Nahirya-Ntege, Patricia; Kekitiinwa, Adeodata (BMC public health, 2018)
Adolescents are a priority group in HIV prevention and treatment. This study sought to determine the prevalence and correlates of HIV testing services (HTS) among adolescents in the pastoralist post-conflict area of Karamoja sub region, Uganda. Methods: A cross sectional study of 1439 adolescents aged 10–19 years, attending nine public health facilities in five of the seven districts of Karamoja, was conducted between August to September 2016. Adolescents were consecutively selected and interviewed using structured interviewer administered questionnaires. All respondents who had never tested for HIV were offered HTS. The main outcome was ever tested for HIV. Correlates of ever tested were analyzed using multivariate logistic regression model. Results: Of the 1439 adolescents, 904 (62.8%) were females, 1203 (83.6%) were aged 15–19 years, 618 (43.0%) had attained primary education and 885 (61.5%) had ever had sex. Overall 1177 (81.8%) had ever tested and received HIV results. Older age (15–19 years) (adj.OR = 2.71, 95% CI: 1.85–3.96), secondary level education or higher (adj.OR = 2.33, 95% CI: 1.33–4.10), and ever had sex (adj.OR = 2.03, 95% CI: 1.42–2.90) were associated with higher odds of HIV testing. Of the 262 who had never tested, 169 (64.5%) accepted testing and 2.4% were HIV positive. Reasons for not accepting the test included fear of being tested and not ready for an HIV test because of perceived suffering HIV positive clients go through. Conclusion: Awareness of HIV status and uptake of HTS among adolescents in this hard-to-reach post-conflict region was high and close to the global UNAIDS target of 90%. However, the HIV prevalence of 2.4% among the non-testers who accepted to be tested was high and emphasises the need for targeted testing to reach the undiagnosed HIV infected adolescents in this region.
Keywords: Adolescents; HIV; HIV testing services; Uganda; Pastoralist communities